ION SERIES AND THE PHYSICAL PROPERTIES OF PROTEINS : III. THE ACTION OF SALTS IN LOW CONCENTRATION. - Loeb, Jacques (The Rockefeller University Press, 1921)
1. Ions with the opposite sign of charge as that of a protein ion diminish the swelling, osmotic pressure, and viscosity of the protein. Ions with the same sign of charge as the protein ion (with the exception of H and OH ions) seem to have no effect on these properties as long as the concentrations of electrolytes used are not too high. 2. The relative depressing effect of different ions on the physical properties of proteins is a function only of the valency and sign of charge of the ion, ions of the same sign of charge and the same valency having practically the same depressing effect on gelatin solutions of the same pH while the depressing effect increases rapidly with an increase in the valency of the ion. 3. The Hofmeister series of ions are the result of an error due to the failure to notice the influence of the addition of a salt upon the hydrogen ion concentration of the protein solution. As a consequence of this failure, effects caused by a variation in the hydrogen ion concentration of the solution were erroneously attributed to differences in the nature of the ions of the salts used. 4. It is not safe to draw conclusions concerning specific effects of ions on the swelling, osmotic pressure, or viscosity of gelatin when the concentration of electrolytes in the solution exceeds M/16, since at that concentration the values of these properties are near the minimum characteristic of the isoelectric point.